Development and Validation of IBSA Photographic Scale for the Assessment of Neck Laxity - Tateo A; Siquier-Dameto G; Artzi O; Humzah D; Molina B; Jain R; Lanzarotti A; Laouedj M; Dapis N; Bellia G (Dove Medical Press, 2021)
Antonello Tateo,1 Gabriel Siquier-Dameto,2– 4 Ofir Artzi,5 Dalvi Humzah,6 Beatriz Molina,7 Ravi Jain,6 Arturo Lanzarotti,8 Malika Laouedj,9 Nicolas Dapis,10 Gilberto Bellia11 1Private Practice, Milan, Italy; 2Private Practice, Amsterdam, the Netherlands; 3Private Practice, Mallorca, Spain; 4Research Group of Clinical Anatomy, Embryology and Neuroscience (NEOMA), Department of Medical Sciences, Universitat de Girona (UdG), Girona, Spain; 5Department of Dermatology, Tel Aviv Sourasky Medical Center, Tel Aviv, Israel; 6Private Practice, London, UK; 7Private Practice, Bristol, UK; 8Research & Development, IBSA Institut Biochimique SA, Lugano, Switzerland; 9Clinical Operations, Quantificare SA, Valbonne, France; 10Business Development, Quantificare SA, Valbonne, France; 11Medical Affair, IBSA Farmaceutici Italia, Lodi, ItalyCorrespondence: Gilberto BelliaIBSA Farmaceutici Italia, Lodi, LO, ItalyEmail gilberto.bellia@ibsa.itObjective: To describe the development and validation of the 5-grade photographic IBSA Neck Laxity Scale.Methods: The scale was developed from 2 real images, which led to the creation of 5 morphed images, representing different degrees of severity of laxity of the neck. For validation, a set of 50 images (25 real and 25 morphed) was created and sent for evaluation to 6 trained raters (physicians) in 2 rounds, 1 month apart. Raters had to assess each image according to the 5-image scale. Inter-rater and intra-rater reliability in both rounds was evaluated.Results: As to intra-rater reliability, single rater kappa scores between 0.69 and 0.87, and a global kappa score of 0.78 were observed. Inter-rater agreement was measured by means of the intra-class correlation coefficient and scores higher than 0.85 were reported, indicating excellent reliability.Conclusion: IBSA Neck Laxity Scale is a validated and reliable scale.Keywords: photographic scale, neck, laxity, aesthetic medicine, scale validation, scale development